Retrofitting of Reinforced Concrete Beams Using a Fiberglass Jacketing System - Titik P. Artiningsih; Lirawati L.; Navi Helmi (Universitas Islam Sultan Agung, 2021)
Building collapse that occurred mostly caused by structure failure in containment earthquake load. Factors that lead to the failure of the beam, among others is beam planning that does not calculate ductility or restraint, resulting decline of beams performance. One way to improve beam strength and ductility are to retrofit the beam by wrapping beams using fiberglass. Research aims to discover the increase amount of bending load capacity from concrete beam that has been retrofitted using jacketing fiberglass. Experimental testing was carried out on beam specimens with a cross section size of 150x200 mm and a length of 1400 mm. Three beam specimens were subjected to bending loads with a three point loading system, with different levels of damage, namely BL1 with collapse at level-1, BL2 at level-2, and BL0 at level-5 as a comparison. Then the BL1 and BL2 were retrofitted by being coated with 2 layers of fiberglass which were glued using epoxy resin. Beams BL-1 and BL-2 are then subjected to a bending test again until they reach level-5 collapse. The test results showed that retrofitted beams were able to increase flexural strength, BL-1 increased 115.15% from the original load and BL-2 increased 52.27% from the original load.